Use of information technology to support integrated water resources management implementation - Shehab, Hisham, author; El-Sharkawy, Moamen, author; Sheng, Tom, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
While progress with Integrated Water Resources Management (IWRM) is fundamental to sustainable development, a prerequisite for furthering this process is an effective computerized system that serves the data and information needs of all stakeholders, and promotes equity through good governance. Developing an IWRM information system is a challenge in developing countries with limited resources. In most developing countries, water information systems at local administrative levels are generally absent or severely degraded, and management decisions are mostly based on unreliable data and information. A lack of data and obsolete data capture and/or information management systems are common issues, resulting in inadequate data/information to support IWRM implementation. An innovative, inclusive approach is required that will unleash the full benefit of a number of powerful technologies to capture, manage, and disseminate water related data and information in a cost effective and sustainable manner. The Egyptian Ministry of Water Resources and Irrigation (MWRI) has a long-term goal of reorganizing internal functions and operations through a process of local governance consolidation and ministry-wide decentralization, including de-evolution of authority to the local government level. With that, the MWRI has adopted a policy to integrate all water management functions at the district level to support the decentralized management process. The USAID/Egypt-funded Livelihood and Income from the Environment (LIFE) Integrated Water Resources Management (IWRM) Project was designed to focus on implementing policy reform measures on a large scale, covering 27 irrigation districts over 1.2 million acres of Egyptian cultivated land. Implementation of the project began in October 2004 with three main objectives: (1) Consolidate MWRI district offices (i.e., irrigation and drainage) (2) Promote stakeholders' participation through the formation of Branch Canal Water Users' Associations (BCWUA), and (3) Support equitable allocation of water resources at the district level. Under the equitable allocation of water resources objective, a series of activities were carried out to support the development of district water information systems. The effort focused on providing technical assistance on the design, construction, and implementation of information systems in support of water management decision making at the 27 irrigation districts. The information systems component of the project consists of two major technologies: database management and digital mapping systems. While the database management and mapping systems evolved independently, both are integrating, analytical, and strategic technologies that are complementary to each other. The convergence of both technologies offers extraordinary opportunities for producing information management tools that connect disparate, but indispensable, threads of spatial and non-spatial data across different information systems and management units. These tools create broader knowledge and understanding for decision makers at the district, directorate, and central levels. This paper will discuss the development of the information systems that comprise the seven database management systems (six tabular and one geospatial) to provide timely information in support of decentralized decision-making for improving water management at the district level. These information systems have now been implemented at the 27 (Integrated Water Management Districts) IWMDs under the project with great success. It is anticipated that the information systems will be introduced and implemented by the MWRI at other districts in the near future.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.